The impact of work engagement and health in Productivity associated with presenteeism: a portuguese study - Sequeira, Mariana Domingues Martins Baltazar (2020)
The present study aims to analyze the impact of different levels of work engagement and health conditions on productivity associated with presenteeism. Data were collected on a daily basis from a Portuguese hotel (n = 72). It showed that more work engagement is associated with more productivity, while more types of illness and risks are associated with higher productivity loss. Furthermore, the study addresses presenteeism costs and discusses some managerial implications of the most reported health condition – stress – and one associated organizational consequence - job burnout. The study also discusses the importance of job demands and job resources at organizations. Keywords: Presenteeism, Engagement, Health, Hospitality